A STUDY ON DIGITAL PAYMENT GATEWAY AND ITS INFLUENCE ON THE INDIAN FINANCE MARKET (International Journal of Food and Nutritional Sciences, 2022)
Digital payment gateways have transformed India's financial landscape, facilitating seamless transactions and promoting financial inclusion. This paper examines the evolution of digital payment gateways, their impact on the Indian finance market, and the role of the Reserve Bank of India (RBI) in this transformation. Utilizing RBI data, this study highlights trends in transaction volumes, user demographics, and the implications for financial inclusion and security.